Region of attraction analysis for adaptive control of wing rock system - Li, Dongyang; Ignatyev, Dmitry; Tsourdos, Antonios; Wang, Zhongyuan (Elsevier, 2021)
This paper introduces a numerical method for region of attraction (ROA) estimation of the adaptive control system in polynomial form. A classical adaptive controller with sigma modification on suppressing the wing rock motion is revisited. Using the nonlinear analysis technique based on the sum of squares optimization, ROA of the origin is computed with respect to the potential measurement error. The obtained result gives a solid guarantee on the allowable initial conditions where the adaptive controller is still able to suppress the wing rock motion. It provides confidence for the adaptive controller operating under some unforeseen conditions in practice.
Keywords: Adaptive control; region of attraction; SOS optimization; wing rock; nonlinear analysis